Advanced musculoskeletal simulation as an ergonomic design method. - Rasmussen, John; Boocock, Mark; Paul, Gunther (Work)
This paper investigates new opportunities for ergonomic design based on advanced computer simulated musculoskeletal modeling. The approach is inspired by the influence that other advanced computer-aided engineering technologies have had on product design. The background to the musculoskeletal modeling approach (AnyBody Modeling System) is briefly explained and illustrated by means of a hand sawing task. Simple design modifications to the handle of the saw provide empirical data about muscle forces on which designers can use to enhance product design. It is concluded that musculoskeletal simulation has the potential to significantly improve ergonomic design of many tools and products that derive their value from interfacing with the human body.